Geologia, mineralogia e afinidades petrológicas dos granitóides neoarqueanos da porção central do Domínio Canaã dos Carajás - OLIVEIRA, Vinícius Eduardo Silva de (Universidade Federal do Pará, 2018)
The central portion of the Canaã dos Carajás domain, located in the northern part of the Carajás province was originally marked by the occurrence of undifferentiated rocks belonging to the Xingu complex and Plaque suite, as well as greenstone belts, mafic rocks of the Pium diopside-norite and high K calc-alkaline leucogranites (Boa Sorte and Cruzadão granites). A semi-detailed geological mapping (1:100.0000) was carried out in the Vila União area and allowed the identification of several deformed granite bodies intrusive in the Mesoarchean units. They correspond to the most expressive unit of the studied area and are composed predominantly of monzogranites with chemical and mineralogical affinity with the Neoarchean A-type granites of the Planalto and Vila Jussara suites. The variable felsic and ferromagnesian minerals contents, as well as the different proportions between them, allowed to distinguish four major groups of granitoids: (i) biotite-hornblende monzogranites (BtHblMzG); (ii) biotite granites and leucogranites (BtLG); (iii) biotite-hornblende tonalites (BtHblTn); and quartz diorites (QD). The tectonic foliation of these rocks follows the regional E-W trend and exhibits high angles (70-85°). Well-developed core and mantle structures in quartz and feldspar crystals, as well as the presence of serrated and irregular contacts between these crystals suggest that dynamic recrystallization occurred at relatively high temperatures (> 500 °C). These rocks exhibit a wide variation in silica content (61.7 – 75.91 wt%), are metaluminous to slightly peraluminous and show affinity with A-type (high HFSE) and ferroan granites. Based on magnetic petrology studies it was possible to distinguish two groups of rocks: (1) granites containing only ilmenite with low magnetic susceptibility values (MS; <0.570 × 10-3 SI), and (2) granites with magnetite as the main iron and titanium oxide mineral and higher MS values (> 1.437 × 10-3 SI). Textural and compositional evidences indicate that magnetite and ilmenite are earlycrystallized phases and titanite has magmatic origin. Amphiboles are calcic and classified as hastingsite, whereas biotites are rich in the annite molecule. The relatively high Fe/(Fe + Mg) ratios found in the amphiboles of the BtHblMzG and BtHblTn varieties indicate that these granitoids were formed under low to moderate fO2 conditions, whereas in the BtLG the lower values of this ratio suggest more oxidizing conditions. Geothermometers point to crystallization temperatures between 830 – 930 °C in the different facies. The high total Al content in the amphibole crystals suggests crystallization at pressures between 400 and 800 MPa, indicating that these granitoids were emplaced at different crustal depths.